859 A Single Center Retrospective Study Comparing Retrograde TibioTaloCalcaneal Nailing vs Open Reduction Internal Fixation of Ankle Fractures in a Comorbid Elderly Population. (19th August 2022) - Oochit, KK; Imran, A; Brown, MJC; Hrycaiczuk, A; Jamal, B
Abstract: Aim: The aim of this paper is to compare the functional outcomes and complication rates of ankle fractures treated with retrograde tibiotalocalcaneal nail (TTC) and open reduction internal fixation (ORIF). Method: Matched cohorts according to age and Charlson Comorbidities Index (CCI) (mean=6) were established by performing a retrospective search of a prospectively collated Bluespier® database for patients within our unit who underwent TTC nailing and open reduction internal fixation (ORIF) for acute trauma from 2015 to 2021. Results: 32 patients (8 males/ 24 females) were identified in both the TTC and ORIF groups with mean ages of 78.4 (55–96) and 78.3 (52–93) respectively. Mean follow-up length was 6 months in both groups. All fractures were classified according to AO classification. 3.1% of fractures were 44A, 71.9% 44B, 25% 44C in the TTC group compared to 3.1% 44A, 59.4% 44B and 37.5% 44C fractures in the ORIF group. Surgical site infection rate was 9.4% in the TTC group compared to 6.3% in the ORIF group. Both groups had a similar implant failure rate of 9.4%. 2/32 (6.3%) suffered from periprosthetic fractures in the TTC group and 1 of them required re-operation. 45% of patients in the TTC group returned to their pre-injury level of mobility compared to 40.6% in the ORIF group at their last follow up. Conclusions: Our study showed that retrograde TTC nailing can be a useful treatment option for ankle fractures in the comorbid elderly, restoring function and enabling return to full weight bearing immediately after surgery.